Efektifitas Aplikasi Pupuk Kandang Ayam dan Bokashi Kayambang terhadap Pertumbuhan dan Hasil Mentimun (Cucumis sativus L.) di Lahan Berpasir - Saijo saijo; Fahruddin Alfianto; Anggi Saputera (J-Plantasimbiosa, 2021)
One of the plants favored by all levels of society is cucumber because the fruit is consumed in fresh form, besides that it is also an ingredient in cosmetics, medicines and can be used as industrial raw materials. The type of research land is sandy soil which has problems, namely poor structure, low water absorption and storage capacity. The aim of this study was to examine the effect of interaction between chicken manure and bokashi Kayambang on the growth and yield of cucumber plants on sandy soil. The study was arranged in a factorial manner, using a Randomized Block Design with 2 treatment factors, 3 levels and 3 repetitions. The research stages started from land preparation, nursery, planting, maintenance, fertilization, maintenance and harvesting. Based on the results of the study, it can be concluded that the plants that were given single treatment with bokashi Kayambang had a very significant effect on plant height at 21 and 28 DAP, number of leaves at 14 DAP, fruit length and number of fruit. While the combination treatment of chicken manure with bokashi Kayambang did not occur in all the observed variables. Cucumber fruit production per hectare using chicken manure treatment 2 t ha-1 and bokashi Kayambang 15 t ha-1 resulted in a weight of 2,911, 6 kg -1